Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Dan Variable Costing (Studi Kasus UKM A. Zaki Bakery Medan) - Gustina Rizky; Marliyah; Kusmilawaty (Politeknik Negeri Padang, 2023)
This study aims to determine the price and differences in the calculation of the cost of goods manufactured by using the calculation of the cost of goods manufactured with the full costing method and variable costing. Based on the calculation of the cost of production using the full costing method is higher than the calculation using the variable costing method. This research uses descriptive qualitative analysis method. The type of data used is secondary data obtained from UKM A. Zaki Bakery, namely in the form of data generated by means of interviews, literature and documentation. The results of this study indicate that UKM A. Zaki Bakery doesn’t take into account all the costs of producing its products, resulting in a calculation of the cost of production, which is IDR 672. If the calculation uses the full costing method, the value is higher, which is IDR 681, compared to the calculation of the cost of production using the variable costing method, which is lower, which is IDR 675, with a difference of IDR 6. This difference is due to the imposition of unapplied factory overhead costs.